PENGARUH LUAS LAHAN, MODAL DAN TENAGA KERJA TERHADAP PRODUKSI USAHATANI NANAS (Studi Kasus: Desa Bulud Kecamatan Passi Barat Kabupaten Bolaang Mongondow) - Nia Martika Mokodompit; Jane Sulinda Tambas; Jelly Ribka Danaly Lumingkewas (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine the effect of land area, capital and labor on pineapple farming production as seen from the results of the pre-survey and farmer's share in Bulud Village. The research was carried out in Bulud Village, Passi Barat District, Bolaang Mongondow Regency from November 2020 to August 2021. The data collection method used the "purposive sampling" method, starting with making a population frame from 40 respondents who owned pineapple farms who had been active continuously for the last 2 years and obtained 15 active owner farmers to be used as research sampling. Data was obtained from primary data by distributing questionnaires to respondents to answer the questions that had been prepared, then secondary data was obtained through related offices/services. The data in this study were analyzed by quantitative description for the research variables used and followed by regression analysis. The regression analysis used is the Cobb-Douglas production function regression analysis. Based on the research results, the factors that have a significant effect on the production of pineapple farming in Bulud Village are the variables of land area and capital, while the variable number of workers has no significant effect on the income of pineapple farming.